2004
DOI: 10.2174/0929867043364504
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Seaweed Polysaccharides as Antiviral Agents

Abstract: Several sulfated seaweed polysaccharides show high antiviral activity against enveloped viruses, including important human pathogens such as human immunodeficiency virus, herpes simplex virus, human cytomegalovirus, dengue virus and respiratory syncytial virus. They can be obtained in major amounts and at low costs, have low toxicity and in some cases, lack anticoagulant effects. Even if the systemic applications have many drawbacks, their structure and mode of action indicate potential for topical uses to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
242
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(254 citation statements)
references
References 1 publication
9
242
1
2
Order By: Relevance
“…Anionic polysaccharides derived from phototrophic microorganisms represent a novel substance group featuring various antiviral activities [7,34]. Here we demonstrated the antiviral activities of two sulphur-containing anionic exopolysaccharides from cyanobacterium A. platensis (TK V3) and from rhodophyt P. purpureum (EPS) against the OPV VACV and ECTV.So far, there have been few reports of anti-OPV polyanionic activities derived from phototrophic microorganisms [8,35].…”
Section: Discussionmentioning
confidence: 82%
“…Anionic polysaccharides derived from phototrophic microorganisms represent a novel substance group featuring various antiviral activities [7,34]. Here we demonstrated the antiviral activities of two sulphur-containing anionic exopolysaccharides from cyanobacterium A. platensis (TK V3) and from rhodophyt P. purpureum (EPS) against the OPV VACV and ECTV.So far, there have been few reports of anti-OPV polyanionic activities derived from phototrophic microorganisms [8,35].…”
Section: Discussionmentioning
confidence: 82%
“…virus activities, many groups reported that sulfated galactans from red seaweeds and ulvan from green seaweeds possessed inhibitory activities against HSV, HCMV, and HIV (Baba, Snoeck et al 1988;Mazumder, Ghosal et al 2002;Damonte, Matulewicz et al 2004). The current observations proved that certain algal polysaccharides could be applied as anti-virus agents.…”
Section: Anti-influenza Virus Activitiesmentioning
confidence: 99%
“…The anti-virus properties of algal polysaccharides have generated great interest with activities reported against a wide range of viruses including human immunodeficiency virus (HIV) (Baba, Snoeck et al 1988), herpes simplex virus (HSV) (Hasui, Matsuda et al 1995), human cytomegalovirus (HCMV) (Damonte, Matulewicz et al 2004), vesicular stomatitis virus (Baba, Snoeck et al 1988), papilloma virus (Pérez-Andino, Buck et al 2009) and influenza A virus (Leibbrandt, Meier et al 2010 Adamantane-based anti-virus compounds such as amantadine and rimantadine have serious side-effects on gastrointestinal and nervous system (Jefferson, Demicheli et al 2006). Using oseltamivir, a viral neuraminidase inhibitor, to treat influenza (von Itzstein 2007) is being confounded by the rise of resistant H1N1 influenza strains and emerging resistant influenza A seasonal strains (Bantia, Parker et al 2001;Matheson, Harnden et al 2008;Shun-Shin, Thompson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the antiviral effect of polysaccharides against the herpes simplex virus (HSV) has been reported (Arad, Ginsberg, & Huleihel, 2006;Damonte, Matulewicz, & Cerezo, 2004;Karmakar, Pujol, Damonte, Tuhin Ghosh, & Ray, 2010;Luescher-Mattli, 2003;Pujol, Carlucci, Matulewicz, & Damonte, 2007) and some of these polysaccharides are currently undergoing either preclinical or clinical evaluation (Kleymann, 2005;McReynolds & Garvey-Hague, 2007). Unlike the widely used acyclovir (ACV)-related nucleoside analogues, which all targeted against viral DNA synthesis, polysaccharides interfere with the attachment of virus to host cell surface by binding to viral envelope glycoprotein (Damonte et al, 2004;Duarte et al, 2001;Neyts et al, 1992;Witvrouw & De Clercq, 1997). In contrast with ACV, which may result in some undesirable complications (Richman et al, 1987) and also induce the emergence of drugresistant viruses (Coen, 1991;Larder, Darby, & Richman, 1989) after prolonged treatment in immunocompromised patients, polysaccharides have the relatively low mammalian toxicity and the novel * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%